Younger and Dissatisfied? Relative Age and Life-satisfaction in Adolescence - Luca Fumarco; Stijn Baert (Global Labor Organization (GLO), 2018)
This is the first study to investigate whether age gaps between classmates (that is, relative age) affect life-satisfaction gaps in adolescence. To this end, we analyse data from the multi-country Health Behaviour in School-Aged Children (HBSC) survey. We find evidence that relative age negatively impacts adolescents' life-satisfaction. A twelve-month age gap decreases life-satisfaction, rated on a 0-10 scale, by 0.3 points. This negative effect is consistent across countries. Finally, this negative effect does not decrease with the increase in absolute age.
Keywords: C26; I21; I31; Z13; 330; Relative age; adolescents; education; Europe; life-satisfaction